2019
DOI: 10.1007/s12035-019-01694-7
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 in Astrocyte Is Important for Neurite Outgrowth and Synaptogenesis

Abstract: In this study, we found that Sp1 was highly expressed in astrocytes, implying that Sp1 might be important for the function of astrocytes. Sp1/GFAP-Cre-ERT2 conditional knockout mice were constructed to study the role of Sp1 in astrocytes. Knockout of Sp1 in astrocytes altered astrocytic morphology and decreased GFAP expression in the cortex and hippocampus but did not affect cell viability. Loss of Sp1 in astrocytes decreased the number of neurons in the cortex and hippocampus. Conditioned medium from primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…Specifically, FGF2, IL5 and SP1, through twelve target proteins, promote cell viability and migration and, on the other side, inhibit apoptosis and organismal death confirming the protective role of hill extract. In addition, a regulatory role of SP1 for neuronal development and synaptogenesis has been suggested in mice astrocytes [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, FGF2, IL5 and SP1, through twelve target proteins, promote cell viability and migration and, on the other side, inhibit apoptosis and organismal death confirming the protective role of hill extract. In addition, a regulatory role of SP1 for neuronal development and synaptogenesis has been suggested in mice astrocytes [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…During gliogenesis, Sp1 was proven to binding to the promoter of GFAP, the expression of which was enhanced ( Yeo et al, 2013 ; Johnson et al, 2016 ). The loss of Sp1 in astrocytes is linked to learning and memory impairment in mice by GFAP decrease ( Hung et al, 2020 ). In our study, propofol increase the proportion of GFAP + cells after induced differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that Sp1 can be of great importance for astrocyte function. They found that Sp1 in astrocytes regulates the expression of several genes that are involved in the neuronal development process such as neurite outgrowth and synaptogenesis ( Augusto-Oliveira et al, 2020 ; Hung et al, 2020 ).…”
Section: The Role Of Astrocytes In Synaptogenesis During Brain Damagementioning
confidence: 99%